(untitled) (BIBECHANA, 2023)
The goal of this study is to develop charred tea waste (CTW) via chemical process for the removal of Cr(VI) from contaminated water. Batch adsorption experiments were conducted as a function of pH, initial concentration, contact time and adsorbent dosage. Characterization of the adsorbent was analyzed by FT-IR and XRD. Maximum adsorption capacity (qm) of the CTW was found to be 85.32 mg/g at optimum pH 2 in 120 minutes. The adsorption on CTW was well fitted to the Langmuir isotherm and the kinetic data is consistent with the pseudo-second order kinetic model. The findings suggest that CTW could be an efficient and promising adsorbent for the removing Cr(VI) from aqueous solution.